Book reviews. - Schroeder, Eunice; Leaver, Robin A. (Notes, 1999)
Reviews the book `The Hymn Tune Index: A Census of English-Language Hymn Tunes in Printed Sources From 1535-1830,' by Nicholas Temperley.